PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL MENGGUNAKAN APLIKASI CANVA PADA PEMBELAJARAN IPS BAGI SISWA SDN CIRACAS 11 PAGI - Alyani, Fitri; Ramandha, Septiana Haliza (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2024)
The background of the research is that there are still many students who do not understand the material conveyed by the teacher, this is because the teacher does not use the media as a support in the learning process in social studies subject to the cultural diversity of my nation. The aim of the study was to analyze the due diligence and student responses to audio-visual-based learning media using the Canva application on the cultural diversity of my people. The research was conducted at SDN Ciracas 11 AM class IV as many as 33 students. The method used is research and development (Research and Development) with a 4D model. The data collection method using a questionnaire was validated by media experts and material experts and in the form of questions directed to students as subjects in this study. The results of the feasibility test were validated by two validators, namely the media validator obtained a percentage value of 96% getting very feasible criteria then the material validator obtained a percentage value of 86% getting very feasible criteria, while in student responses obtained a percentage of 92% very feasible criteria . Based on the results of the assessment, it can be concluded that audio-visual learning media using the Canva application which is packaged into learning videos on the cultural diversity of my people for class IV at SDN Ciracas 11 is very feasible to use.